Effects of fatigue on golf performance - Higdon, N. R.; Finch, W. H.; Leib, D.; Dugan, E. L. (Sports Biomechanics, 2012)
The purpose of this study was to determine if body position, weight transfer, and/or pelvis/trunk rotations changed as a result of a golf specific fatiguing protocol and whether these changes affected resultant club head velocity at impact and shot consistency. Six male golfers and one female golfer participated in the study, who had a mean age, height, and body mass of 23.9 ± 3.9 years, 177.4 ± 4.9 cm, and 75.3 ± 9.9 kg, respectively. Path analysis was used to determine the relationships between fatigue, biomechanical variables, and resultant club head velocity at impact and shot consistency. In the statistical models representing the effects of biomechanical variables calculated at the top of the swing and ball contact, golf specific fatigue was associated with a 2.0% and 2.5% reduction in the club head velocity and a 7.1% and 9.4% improvement in the shot consistency, respectively. These data suggest that golf specific fatigue was not related to the initial lower body sagittal plane angles at address nor was simulated golf specific fatigue related to peak transverse plane pelvis and trunk rotational velocities (or their timings) in a manner that indicates a relationship to resultant club head velocity and shot consistency.